Effect of hydrogen peroxide as treatment for amoebic gill disease in Atlantic salmon (Salmo salar L.) in different temperatures. (21st February 2018) - Martinsen, Kristine Hov; Thorisdottir, Audur; Lillehammer, Marie
Abstract: Amoebic gill disease (AGD) is a pathogenic disease in salmonids caused by Neoparamoeba perurans . Treatment of AGD infection has been through freshwater bathing of the fish. However, as the availability of fresh water is often limited, hydrogen peroxide has been introduced as an alternative treatment. This study investigated the effect of hydrogen peroxide as treatment for AGD‐infected salmon ( Salmo salar L., ) at different seawater temperatures and hydrogen peroxide dosages. In total, 600 fish were challenged with N. perurans and the severity of the AGD infection was measured using a gill score scale. After challenge and disease development, the fish were distributed into 12 tanks. The treatment was performed at different seawater temperatures (8°C, 12°C, 17°C) using different hydrogen peroxide doses. Each temperature included an untreated control group. Linear models were used to analyse gill score. A significant effect of treatment was found (−0.68 ± 0.05) regardless of dose and temperature, suggesting that hydrogen peroxide was effective in treating AGD. When the model included dose, a negative linear relationship between dose and gill score was found. The study proved that treatment of AGD with hydrogen peroxide was successful, as gills partially recovered following treatment and further disease development was delayed.